Penerapan Pendekatan TaRL Berbantuan Media Papan Diagram untuk Meningkatkan Hasil Belajar Matematika Siswa SD - Afidatul Muniroh; Bekti Wirawati; Darsono Darsono (CV. Alim's Publishing, 2024)
The mathematics learning results of grade IV students of SDN Dukuh Kupang II/489 Surabaya were initially still relatively low, there were still many students who had difficulties with the concept of presenting bar chart data. For this reason, the researcher conducted a study with the aim of finding out the improvement of student learning results by using the Teaching at The Right Level (TaRL) approach in grade IV mathematics learning at SDN Dukuh Kupang II/489 Surabaya. This research uses the type of Classroom Action Research (PTK). The subject of the study was 28 students in class IV. In the 1st cycle stage, only 32.2% of students achieved the completeness of learning results, this percentage then experienced a significant increase to 82.1% in the 2nd cycle. Based on this study, it can be concluded that the Teaching at The Right Level (TaRL) approach can improve student learning results in mathematics subjects, especially data presentation materials in grade IV of SDN Dukuh Kupang II/489 Surabaya.